Kinesio taping treatments in shoulder impingement syndrome: A systematic literature review - Kamijantono, Harry; Sebayang, Moriko Madadoni; Lesmana, Andrean (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Shoulder impingement syndrome is a musculoskeletal condition that often causes pain and limitation of motion in the shoulder, which is generally caused by pressure on the soft tissue structures around the shoulder joint. Kinesiology tape, as one of the relatively new physical therapy methods, has attracted attention in the context of sports rehabilitation and pain management. Purpose: To evaluate the effectiveness of using kinesiology tape in the management of shoulder impingement syndrome through a systematic literature review. Method: Using a systematic approach, this study identified the strengths and weaknesses of the existing findings and assessed the methodological quality of the published studies. This study collected and analyzed various relevant studies to determine the effects of kinesiology tape on reducing symptoms of shoulder impingement syndrome, improving joint function, and accelerating the recovery process. Results: The review showed that while some studies reported significant benefits from the use of kinesiology tape, the quality of existing evidence was variable and required further research for confirmation. Conclusion: This study provides valuable insight into the role of kinesiology tape in the therapy of shoulder impingement syndrome and suggests future research directions to clarify its effectiveness and mechanism of action.